Captive breeding of Margaritifera auricularia (Spengler, 1793) and its conservation importance - Nakamura, K. (2019)
Margaritifera auricularia is one of the most endangered freshwater mussels (Bivalvia, Unionida) in the world. Since 2013, the abundance of this species in the Ebro River basin (Spain) has sharply declined, driving the species to the verge of regional extinction. Therefore, any management measures that might facilitate the recovery of this species would be essential for its conservation. During 2014–2016, captive breeding of M. auricularia allowed the production of >106 juveniles, out of which 95% were released into the natural environment, and 5% were grown in the laboratory under controlled conditions. The aim of this experimental work was to establish the best culture conditions for the survival and growth of M. auricularia juveniles in the laboratory. The experiment was divided into two phases: phase I, in which juveniles recently detached from fish gills were cultured in detritus boxes until they reached a shell length of 1 mm; and phase II, in which these specimens were transferred to larger aquaria to grow up to 3–4 mm. The best experimental conditions for juvenile survival and growth corresponded to treatments in glass containers at a density of 0.2 ind. L−1, using river water, with added substrate and detritus, enriched with phytoplankton, and avoiding extra aeration. The highest survival and growth rates attained, respectively, values of c. 60% at 100 days and 2.56 mm in shell length at 30–32 weeks. This is the first study to report on the long‐term survival and growth of juvenile M. auricularia in the laboratory, providing essential information in order to implement future conservation measures addressed at reinforcing the natural populations of this highly threatened species in European water bodies.